Mindfulness for smoking cessation - Jackson, S; Brown, J; Norris, E; Livingstone-Banks, JE; Hayes, E; Lindson, N (Wiley, 2022)
Background Mindfulness‐based smoking cessation interventions may aid smoking cessation by teaching individuals to pay attention to, and work mindfully with, negative affective states, cravings, and other symptoms of nicotine withdrawal. Types of mindfulness‐based interventions include mindfulness training, which involves training in meditation; acceptance and commitment therapy (ACT); distress tolerance training; and yoga.